Influence of Welding Parameters on Strength of Metal Inert Gas Welded Mild Steel Joints - Obura, Washington Odhiambo; Mayaka, Abel N.; Ondieki, Charles M. (International Journal of Computing and Engineering, 2024)
Purpose: MIG welding is a type of arc welding that uses a continuous solid wire electrode and a shielding gas to join two metals by heating them with an electric arc. Process parameters including current, voltage, preheat temperature and post-weld heat treatment were studied. Then, optimize process parameters of experiments done in previous work using a Taguchi Orthogonal Array (L27) design. Methodology: A grey based Taguchi method is used to optimize the process parameters. The analysis of variance (ANOVA) is applied to assess the significance of the input parameters on the response parameters. A mathematical model is developed using multiple linear regression equations. Findings: Results of this research show that it is possible to get higher strengths of weld joints using Taguchi design. Increasing current (I) and post-weld heat treatment temperature (PWT) increases strength of the studied welded joints, and vice versa. Unique contribution to theory, policy and practice: Future research should validate the findings of the current research through experimental investigations.